English - Bajčetić, Miloš; Pešikan, Ana; Milutinović, Katarina; Ilijevski, Ana; Leković, Aleksa; Rakočević, Jelena; Zaletel, Ivan (Medical Research, 2024)
Peer-assisted learning (PAL) is a form of teaching method where students facilitate the transfer of knowledge to other students and in the same time learn themselves. Department of Histology and Embryology at the Faculty of Medicine, University of Belgrade, Serbia has a longstanding tradition of (PAL), which involves the use of undergraduate teaching assistants (UTAs) in practical microscopy classes. The aim of this research was to evaluate the attitudes and opinions towards UTAs work in the course of Histology and Embryology from the perspective of 1st year students. Data from this study were collected from 512 undergraduate medical students enrolled in the 1st study year using an anonymously semi-structured questionnaire. Analysis of student’s responses has shown that almost all of our students have asked for the help of UTAs during the course of Histology and Embryology. Additionally, 65% of students have said that they felt more comfortable to ask UTAs for help during their labs than faculty teachers. Majority of students believe that UTAs have devoted sufficient time to them during practical classes. Nearly 90% of students agreed that UTAs have given them good advices and answers and more than 80% perceived that they had never received inaccurate information from UTAs. More than 40% of students are able to see themselves in the role of UTAs in the future. These results indicate that UTAs have a significant place in the Histology and Embryology curriculum and that their role in everyday teaching represents one of the most important aspects of PAL.